Ensaios sobre o ensino profissionalizante no Ceará - Mariano, Francisca Zilânia (2016)
This thesis comprises three articles. The first, titled "Evaluation of Vocational Education with Longitudinal Data", aims to broaden the debate in the literature of the Economy of Education on public education, by assessing the performance of the students of State Schools of Vocational Education (EEEP) of Ceará in the five areas of the ENEM examination of 2014. Some contributions may be considered: methodological procedures for obtaining and using longitudinal data; Application of the CEM algorithm and conduction of the evaluation through the Lasso and post-Lasso methods in the process of variable selection for estimation of the propensity score matching (PSM) model. It is concluded that the average treatment effect is positive and significant in each area of the exam and in the general average of the ENEM, particularly in Writing, whose effect is 39.9% higher in the grade of an EEEP student. By isolating the school net effect, EEEP demonstrate to possess more effective guidelines in potentializing cognitive knowledge abilities relative to regular schools, under the hypothesis that the variables not considered in the analysis are equivalent between the two types of school. These results contribute to supporting future decisions of educational policy makers. The second article, "Unconditional Quantile Decomposition of Performance Differences between Vocational and Private Education," embodies new evidences on performance differentials between students of public vocational and private schools in the distribution of grades in the ENEM examination. In addition to proposing a new construction for the group of public schools, the empirical application is distinguished by the use of the Unconditional Quantile Regression method based on the recentered influence function (RIF) with a reweighting procedure, besides allowing the application of the Oaxaca–Blinder decomposition. Positive and significant differences are found in all areas of the exam in favor of private schools’ students, especially in Writing, whose differentials are the highest throughout the distribution, ranging from 12% to 16%. By decomposing the effects, it is found that the unobservable ones are positive and significant in all the quantiles of the distribution and in all areas of the ENEM, besides explaining most of the differentials of the grades, especially in mathematics, whose effect grows with the quantile of the distribution (glassceiling). Since the characteristic effect turns out to be negative only in the bottom of the grade distribution, it is concluded that private schools’ students present better characteristics that contribute to explain their higher grades in the exam. The third article, "Vocational Education and Labor Market Insertion", contributes to the scarce debate in the Brazilian literature about the connection between vocational vis a vis regular education and the labor market. In this sense, new evidences are drawn about the youngsters’ choice for specific specializations available in the EEEP and their positions in the labor market. Based upon a sample with longitudinal information created by the junction of three databases – School Census/2011/2012 and The Annual Relation of Social Information (RAIS/2013) – the methodology that combines the entropy method with PSM procedure is applied for the binary treatment variable, and the PSM with multiple treatments for the categorical treatment variable. In order to allow for statistical treatment, due to the excessive amount of 596 occupations listed in the Brazilian Classification of Occupations (CBO, 2002), the Jannuzzi procedure (2001, 2003) is applied to regroup them in only five socioeconomic occupational categories. It is concluded that the effect of vocational training is not significant on the earnings of high school students specialized in occupational category of Health. On the other hand, the effects are positive and significant in Management occupational category, with a differential of more than 100% compared to the group of regular schools, while the effects in the category of Information are significant and negative. It is also verified that the effects on earnings were positive and significant only for students who took courses in Health and Management, with differentials of 12% and 8%, respectively, over the others. It is also worth noting the higher proportion of students present in the two occupations that require more qualified training relative to the other three.